2017
DOI: 10.1016/j.kjms.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Development and in vivo evaluation of self‐microemulsion as delivery system for α‐mangostin

Abstract: α-Mangostin (MG) is a versatile bioactive compound isolated from mangosteen and possesses significant pharmacokinetic shortages. To augment the potential clinical efficacy, MG-loaded self-microemulsion (MG-SME) was designed and prepared in this study, and its potential as a drug loading system was evaluated based on the pharmacokinetic performance and tissue distribution feature. The formula of MG-SME was optimized by an orthogonal test under the guidance of ternary phase diagram, and the prepared MG-SME was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…The nanomicelle uptake was mediated by endocytosis, a finding that indicated intracellular delivery of α-mangostin that could be associated with potential cytotoxicity (IC 50 of 8.9 ± 0.2 μg/mL). 82 Chitosan, PLGA Colloidal extraction solvent evaporation [75] PEG, PLA Emulsion/solvent evaporation techniques [76] PLGA Double emulsion solvent evaporation method [42] EC-MC Spray drying [77] Chitosan, alginate and genipin Ionotropic gelation method [78] β-cyclodextrin Inclusion complex technique [79] β-cyclodextrin-chitosan Inclusion complex [80] β-cyclodextrin Inclusion complex [81] Nanomicelles PVP Solvent evaporation method [82] MPEG and PLA Single-step self-assembly method [83] MPEG and PCL Self-assembly method [84] Liposome nanoparticles Transferrin Thin film hydration [85] Soya lecithin Phase separation coacervation method [86] Cholesterol, Tween 60 and ethanol Film hydration method [87] Solid lipid nanoparticles Lavender essential oil and cetyl palmitate Hot and high-pressure homogenisation techniques [88] PLGA and CD44 thioaptamer Nanoprecipitation combined with self-assembly [89] Nanofibres Thiolated chitosan Electrospinning [90] PVP Electrospinning [91] Metal nanoparticles Ag (silver) Chemical reaction by using silver nitrate (AgNO3) [92] Gold, PEI, cyclodextrin and tanshinone Chemical reaction using polyethyleneimine (PEI) [93] Emulsion nanoparticle Captex 200 P, Tween 80, carbopol 90 and silica Solid self-emulsification [94] Oleic acid, isopropyl myristate, Cremophor EL, Tween 80, carboxymethylcellulose sodium Self-microemulsion [31] In another study, α-mangostin nanomicelles with methoxypoly(ethylene glycol)-poly(lactide) (MPEG-PLA) were developed by a single-step self-assembly method for malignant glioma. In vitro and in vivo assays showed that the α-mangostin/MPEG-PLA nanoparticles inhibited cell growth and induced apoptosis-with cleaved caspase expression, DNA fragmentation, downregulation of antiapoptotic molecules and up-regulation of apoptotic molecules.…”
Section: Nanomicellesmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanomicelle uptake was mediated by endocytosis, a finding that indicated intracellular delivery of α-mangostin that could be associated with potential cytotoxicity (IC 50 of 8.9 ± 0.2 μg/mL). 82 Chitosan, PLGA Colloidal extraction solvent evaporation [75] PEG, PLA Emulsion/solvent evaporation techniques [76] PLGA Double emulsion solvent evaporation method [42] EC-MC Spray drying [77] Chitosan, alginate and genipin Ionotropic gelation method [78] β-cyclodextrin Inclusion complex technique [79] β-cyclodextrin-chitosan Inclusion complex [80] β-cyclodextrin Inclusion complex [81] Nanomicelles PVP Solvent evaporation method [82] MPEG and PLA Single-step self-assembly method [83] MPEG and PCL Self-assembly method [84] Liposome nanoparticles Transferrin Thin film hydration [85] Soya lecithin Phase separation coacervation method [86] Cholesterol, Tween 60 and ethanol Film hydration method [87] Solid lipid nanoparticles Lavender essential oil and cetyl palmitate Hot and high-pressure homogenisation techniques [88] PLGA and CD44 thioaptamer Nanoprecipitation combined with self-assembly [89] Nanofibres Thiolated chitosan Electrospinning [90] PVP Electrospinning [91] Metal nanoparticles Ag (silver) Chemical reaction by using silver nitrate (AgNO3) [92] Gold, PEI, cyclodextrin and tanshinone Chemical reaction using polyethyleneimine (PEI) [93] Emulsion nanoparticle Captex 200 P, Tween 80, carbopol 90 and silica Solid self-emulsification [94] Oleic acid, isopropyl myristate, Cremophor EL, Tween 80, carboxymethylcellulose sodium Self-microemulsion [31] In another study, α-mangostin nanomicelles with methoxypoly(ethylene glycol)-poly(lactide) (MPEG-PLA) were developed by a single-step self-assembly method for malignant glioma. In vitro and in vivo assays showed that the α-mangostin/MPEG-PLA nanoparticles inhibited cell growth and induced apoptosis-with cleaved caspase expression, DNA fragmentation, downregulation of antiapoptotic molecules and up-regulation of apoptotic molecules.…”
Section: Nanomicellesmentioning
confidence: 99%
“…The targeted system and high oral bioavailability of α-mangostin with self-microemulsion provides excellent performance for clinical drug efficacy. 31…”
Section: Emulsion Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…α-MG was universally distributed into almost all organs, including the liver, kidney, and brain. This study demonstrated that the microemulsion was an efficient delivery system for α-MG to cross BBB [ 115 ]. Another proposed delivery system was transferrin-modified liposomes (Tf(α-MG) liposome) administered through i.v.…”
Section: Pharmacokinetic (Pk) Profiles Of Mp-derived Agentsmentioning
confidence: 99%
“…and i.v. administrations may not be appropriate to apply to the actual treatment regimen of AD in humans [ 115 ]. Oral administrations of α-MG may possess limitations due to its hydrophobic nature, poor aqueous solubility and stability, low bioavailability, and lack of accumulation in the target organs including brain [ 116 , 117 ].…”
Section: Pharmacokinetic (Pk) Profiles Of Mp-derived Agentsmentioning
confidence: 99%